Psycho killer - Von Ziegesar, Cecily (Gossip girl novels., 2011)
An uproarious horror-spin adaptation of the first Gossip Girl tale finds Serena returning from boarding school determined to make amends to Blair Waldorf by eliminating Nate Archibald, a plot that Blair counters with her own plans to get rid of everyone who ever irritated her.